"On the Development of Terrortory". (August 2020) - Brayboy, Bryan Mckinley Jones; Chin, Jeremiah
Deploying Indigenous imagery without including Indigenous peoples perpetuates the idea that these communities are of the past, erasing them from the present. Here, the authors explain it as "terrortory", or the lawful use of fear and violence to alienate peoples and land for power.